Psychosocial Screening Among Youth Seeking Weight Management Treatment. (March 2018) - Ratcliff, Megan B.; Catlin, Perry A.; Peugh, James L.; Siegel, Robert M.; Kirk, Shelley; Tamm, Leanne
The objectives of this study were to identify rates of, and factors associated with, "at-risk" scores on a brief psychosocial screener among overweight/obese youth seeking weight management treatment, as well as concordance between youth and caregiver reports. A retrospective chart review of 1443 consecutive patients ages 4 to 18 years and their caregivers was conducted. Almost 1 in 4 youth with overweight/obesity presented with psychosocial symptoms in the at-risk range for significant mental health issues based on caregiver report on the Pediatric Symptom Checklist (PSC) and 1 in 6 based on youth self-report on the Youth Pediatric Symptom Checklist (Y-PSC). Concordance between caregiver and youth was fair (agreement 24% to 40%). Higher scores were associated with male sex and older age on the PSC and with indication of depressive disorder in the electronic medical record on the Y-PSC. Conducting a brief psychosocial screen in comprehensive weight management programs is feasible and clinically indicated.